Reforming Procedures for Assessing Research Protocols During Covid-19 Pandemic - Susilawati, Tri Nugraha; Cahyanto, Erindra Budi; Sudarmaji, Usman (PAEDAGOGIA, 2023)
: Covid-19 pandemic has caused dramatic changes in daily activities. In particular, human interactions were limited, and most daily duties were directed into an online environment. This study aimed to describe the characteristics of research protocols submitted to the Research Ethics Committee (REC), Faculty of Medicine, Universitas Sebelas Maret (UNS), and evaluate the effectiveness of ethical review procedures implemented during the pandemic era. The following data were retrieved: protocol identity, researcher's institution, researcher's educational background, type of study, the date of protocol submission, and the date when the ethical clearance (EC) certificate was issued. Two hundred seventeen research protocols were submitted to the REC from 1 January 2021 until 30 June 2022. Most researchers were university students, lecturers, physicians, and service providers. Observational studies were more prevalent than interventional studies. The ethical reviews were usually completed within 2-3 weeks unless a few protocols required major revisions. Most applicants and reviewers were satisfied with the process of online review. The REC secretariat played a crucial role in keeping everyone working on schedule. In conclusion, restricting direct human interactions during the COVID-19 pandemic does not affect the ethical review process. With familiar tools, online review becomes more effective than face-to-face meetings.